2010
DOI: 10.1007/s12038-010-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clonal diversity of the endemic ant-plant Humboldtia brunonis (Fabaceae) in the Western Ghats of India

Abstract: Humboldtia brunonis (Fabaceae, Caesalpinioideae) is a dominant self-incompatible ant-plant or myrmecophyte, growing as an understorey tree in high-density patches. It is endemic to the biodiversity hotspot of the southern Western Ghats of India and, besides ants, harbours many endemic invertebrate taxa, such as bees that pollinate it as well as arboreal earthworms, within swollen hollow stem internodes called domatia. Using inter simple sequence repeat (ISSR) markers, three geographically separated populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…The values of Simpson's diversity index (D) in all but one (BK) populations examined were considerably high (Table 5) relative to mean value for clonal plants (D = 0.62 [28]; D = 0.75 [39]). Similarly high geno typic diversity indices were reported for the popula tions of other vine species, Pueraria lobata [22], Mon itopetalum chinense, and clonal plant Humboldtia brunonis [40]. All localities examined in the present study were multiclonal.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…The values of Simpson's diversity index (D) in all but one (BK) populations examined were considerably high (Table 5) relative to mean value for clonal plants (D = 0.62 [28]; D = 0.75 [39]). Similarly high geno typic diversity indices were reported for the popula tions of other vine species, Pueraria lobata [22], Mon itopetalum chinense, and clonal plant Humboldtia brunonis [40]. All localities examined in the present study were multiclonal.…”
Section: Methodssupporting
confidence: 86%
“…At the species level, the value of G/N index consti tuted 0.377. Upon maximum genotypic diversity, the value of G/N was equal to one, i.e., in this case each plant represents an independent genet [27], and it can be treated as an indicator of sexual propagation, as it was reported for Humboldtia brunonis [40]. Corre spondingly, the level of sexual propagation for A. con torta constituted 37.7%, and the level of clonal repro duction, 62.3% (1-G/N).…”
Section: Methodsmentioning
confidence: 94%
“…Humboldtia brunonis (Fabaceae) is a dominant understorey tree, 6–10 m tall, endemic to the low elevation, tropical, wet evergreen forests of the Western Ghats of India (Ramesh & Pascal ) and found in a narrow mountainous strip between 11°10′N and 13°45′N. The plant is clonal with a maximum distance of 8·75 m between any two neighbouring non‐clones (Dev, Shenoy & Borges ). It occurs in dense patches of about 0·25 km 2 (J. Chanam, pers.…”
Section: Methodsmentioning
confidence: 99%
“…These sites span a rainfall seasonality gradient in the Ghats with longer dry seasons (8 mo) towards the north compared with the south (6 mo) since the southern Western Ghats receive rain from both the south-west monsoon (June-September) as well as the north-east or retreating monsoon (October-November) (Davidar et al 2005, Gadgil & Joshi 1983, Pascal 1988 and also suggested a natural geographical grouping between northern sites: Agumbe and Kudremukh, and southern sites: Uppangala, Sampaje and Solaikolli. Humboldtia brunonis occurs in clonal clumps (Dev et al 2010) and is so abundant that it features within two forest type associations: (1) Dipterocarpus indicus-Humboldtia brunonis-Poeciloneuron indicum type, and (2) Dipterocarpus indicus-Kingiodendron pinnatum-Humboldtia brunonis type (Pascal 1988, Rai 2000. Agumbe and Kudremukh occur within the first, and the other three sites within the second forest type.…”
Section: Study System and Sitesmentioning
confidence: 99%